2014
DOI: 10.3382/ps.2013-03404
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antibiofilm effects of selected food preservatives against Salmonella spp. isolated from chicken samples

Abstract: Salmonella spp. are widespread foodborne pathogens that contaminate egg and poultry meats. Attachment, colonization, as well as biofilm formation capacity of Salmonella spp. on food and contact surfaces of food may cause continuous contamination. Biofilm may play a crucial role in the survival of salmonellae under unfavorable environmental conditions, such as in animal slaughterhouses and processing plants. This could serve as a reservoir compromising food safety and human health. Addition of antimicrobial pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…S. enterica strains had a MIC for sodium nitrite (10,000 mg/kg) and sulfite (50,000 mg/kg) significantly higher than values allowed for these additives in meat [ 3 ]. In the same way, the results of this study differ from those of Buket et al [ 22 ], who obtained a MIC of 250 mg/kg for a S. enterica strain, a value much lower than our results. The differences between these two studies could be due to the presence of determinate mechanisms in the Salmonella strains tested, allowing for a better tolerance to sodium nitrite.…”
Section: Discussioncontrasting
confidence: 99%
“…S. enterica strains had a MIC for sodium nitrite (10,000 mg/kg) and sulfite (50,000 mg/kg) significantly higher than values allowed for these additives in meat [ 3 ]. In the same way, the results of this study differ from those of Buket et al [ 22 ], who obtained a MIC of 250 mg/kg for a S. enterica strain, a value much lower than our results. The differences between these two studies could be due to the presence of determinate mechanisms in the Salmonella strains tested, allowing for a better tolerance to sodium nitrite.…”
Section: Discussioncontrasting
confidence: 99%
“…All other positive antibiofilm activities were not influenced by antibacterial activity. Determinations of antibacterial together with antibiofilm activities were suggested by Er et al (2014). They reported that some food or feed preservatives such as ciprofloxacin, sodium nitrite and potassium sorbate had more antibacterial than those antibiofilm activities which should be considered for the possibility the cause of resistency.…”
Section: Biofilm Inhibition Activitymentioning
confidence: 99%
“…Er et al (2014) compared the differences in the susceptibility of Salmonella in the planktonic and biofilm forms to preservative agents including MP and PP, and found that the resistance of Salmonella in biofilm form was greater than that in planktonic form. In addition, parabens were found easily degradated in the environment.…”
Section: Effects On Bacteriamentioning
confidence: 99%
“…Parabens (esters of 4-hydroxybenzoic acid) are a group of antimicrobial preservatives extensively used in pharmaceuticals and personal care products (PPCPs) and in food products (Er et al 2014;Liao et al 2013a;Melo and Queiroz 2010). As a consequence, parabens are frequently detected in the environment (Jonkers et al 2009;KasprzykHordern et al 2008;Renz et al 2013).…”
Section: Introductionmentioning
confidence: 99%